(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
The area of Dohuk city in 1967 was 1.0 km2, and then it expanded until it reached 6.94 km2 in 1987, then 41.64 km2 in 2022, and thus it extends over 12 geological formations. the city extended upon 12 various, heterogeneous formation and sedimentation which have different response to geomorphic processes, slope deposit consisting highest area 46.9 km2, lowest formation area is Aliji formation 2.6 km2, Mountains encircle the City from all directions except the west, Baikhair mount from the North, Dohuk mount from south, Mamsin from East, elevation of area between 1100 - 440m, Slope degree is between 0 - 87.9°. There are 6 Geomorphic units, and the highest unit area is Alluvial fan 63.84 km2, lowest unit area is a flood plain 2.94 km2. The extension of the city in 1967 was limited for two geomorphic units, the floodplains and the accumulative glacis, in 1987, The city extended to new geomorphic units, which are fluvial fans, and in 2022, the city expanded to the previous geomorphic units, in addition to its extension on geomorphic units with higher elevations and slopes than its formers, which are 545the pediments and mountains. Finally, the results of urban geomorphology studies can be taken into account in the context of systematic and comprehensive scientific planning rather than the random and ill-considered expansion of the city.